Clinical and Demographic Characteristics of Patients Hospitalized for Decompensated Heart Failure with Extremely High NT-proBNP Levels - Ruxandra Maria Christodorescu; Daniel Miron Brie; Alina Diduța Brie; Samuel Nistor; Alexandru Tîrziu; Angela Dragomir; Cristian Mornoș; Simona Drăgan; Daniel Duda-Seiman; Adina Pop-Moldovan; Dan Dărăbanțiu (Diagnostics)
Background: NT-proBNP levels with a wide range at admission play both a diagnostic and a prognostic role in patients with HF. The differences regarding the clinical profiles and demography in decompensated HF patients according to NT-proBNP levels at admission are not clear. Methods: This study aimed to analyze and compare clinical profiles and demographics in patients hospitalized for decompensated heart failure according to levels of NT-proBNP at admission. The study included 302 patients hospitalized for decompensated HF who were divided into three groups based on admission NT-proBNP levels: group A (n = 46, with NT-proBNP level < 3000 pg/mL), group B (n = 130, NT-proBNP level between 3000–10,000 pg/mL), and group C (n = 126, NT-proBNP level > 10,000 pg/mL). Results: Patients hospitalized with decompensated HF and very high levels of NTproBNP, above 10,000 pg/mL at admission, are older, have a lower LVEF, higher NYHA class, more renal dysfunction, and longer hospital stay, resulting in a more severe clinical profile. Conclusions: The presence of very high levels of NT-proBNP may identify a category of patients with a more severe prognosis that requires more aggressive management and closer follow-up.